Cavity with distributed dielectric coating for subterahertz second-harmonic gyrotron - Shcherbinin, V.I.; Zaginaylov, G.I.; Tkachenko, V.I. (Вопросы атомной науки и техники, 2016)
Metallic cavity with distributed dielectric coating for the 0.4 THz second harmonic gyrotron is proposed and studied using the generalized scattering matrix approach. It is shown that such coating provides several-fold increase in the Q-value of the operating mode with respect to that of the fundamental competing mode at a reasonable level of ohmic losses, dielectric losses and mode conversion.